2004
DOI: 10.1111/j.1368-5031.2004.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasmapheresis in patients with severe hyperthyroidism in whom antithyroid drugs are contraindicated

Abstract: Four patients with Graves' disease in whom antithyroid drugs could not be used were treated by plasmapheresis preoperatively. On admission all patients had severe hyperthyroidism. All patients were treated by beta blockers, cholestyramine and inorganic iodine before plasmapheresis. Plasmapheresis course consisted of three sessions. Removed plasma was replaced by a synthetic colloid solution and human albumin other than fresh-frozen plasma. Plasmapheresis led to decreases in serum T3 concentrations >78-40% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 26 publications
2
53
1
4
Order By: Relevance
“…However, in patients with iatrogenic thyrotoxicosis or for whom antithyroid drugs are contraindicated or who are resistant to antithyroid drugs, further therapies are needed to restore euthyroid hormone status. The reported cases suggested that therapeutic plasma exchange (TPE) has been used as an additional treatment or preparation for surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 97%
“…However, in patients with iatrogenic thyrotoxicosis or for whom antithyroid drugs are contraindicated or who are resistant to antithyroid drugs, further therapies are needed to restore euthyroid hormone status. The reported cases suggested that therapeutic plasma exchange (TPE) has been used as an additional treatment or preparation for surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 97%
“…Other treatment options include plasmapheresis and therapeutic plasma exchange, which can quickly reduce the levels of thyroid hormone within several hours (9). This can be considered in cases of exogenous thyroid hormone ingestion, when euthyroidism needs to be restored very quickly, or when the patient has contraindications to all other therapeutic options (10,11). Another choice is oral cholestyramine resin, which binds to T4 and T3, preventing enterohepatic recirculation, leading to excretion (9).…”
Section: Discussionmentioning
confidence: 99%
“…Öz-bey ve ark. (11) dört Graves hastasında plazmaferezin serum T3 konsantrasyonunu % 40-78, FT4 düzeyini ise % 69 oranında azalttığını ve tiroidektomiye yakın sonuçlar elde ettiklerini bildirmişlerdir. Güvenç ve ark.…”
Section: Ft3: Serbest Tri-iyodotironin Ft4: Serbest Tetra-iyodotironunclassified